Penilaian kualitas kortikal mandibula pasien diabetes mellitus tipe 2 dengan analisis radiomorfometrik pada radiograf panoramik - Annisa Putri; Aga Satria Nurrachman; Lusi Epsilawati; Azhari Azhari (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This research aims to evaluate radiological finding on bone of patients with T2DM (type 2 Diabetes Mellitus) by evaluating mandibular cortical quality using radiomorphometric assessment specifically MCI (Mandibular Cortical Index) and AI (Antegonial Index). Material and Methods: This research is a descriptive analytic cross-sectional study, populations and samples using secondary data radiographs of T2DM patients that have been proven by medical statement from a doctor and normal sample were selected according to specified criterias. Results: It showed between group consisting of patients with T2DM and another one with normal patients, both have dominant result of MCI assessment type C2. While the result of Antegonial Index assessment there were a difference of cortical thickness between two groups. The average AI value from normal patients were 4,179 with standard deviation of 0.420, while another group with T2DM were 3,641 with standard deviation of 0.477. Conclusion: Based on the results of the study, it was found that there has been a significance difference of cortical bone qualities between two groups of samples which can be seen from the result of Antegonial Index, a T2DM patients has average values lower than normal patients, while for the results of MCI assessment between two groups have similar types.